FORMATION OF EDUCATION MANAGEMENT INFORMATION SYSTEM AS A STAGE OF MODERNIZATION OF PUBLIC ADMINISTRATION INFORMATION SUPPORT IN THE BRANCH OF EDUCATION IN UKRAINE - Vatkovska M.G., (Pressing Problems of Public Administration, 2015)
Author conducted analysis of the formation of management information system of educationin Ukraine. It is stressed that education management information system provides not only aprinciple of interaction between all actors of the educational process, but a different model ofpublic administration.